Tragedi Keluarga Nuh dan Pengabaian Anggota Keluarga: Tafsir Kejadian 9:18-29: Noah's Family Tragedy and Family Members Abandonment: A Commentary on Genesis 9:18-29 - Firman Panjaitan; Dwi Ratna Kusumaningdyah (Sekolah Tinggi Teologi Baptis Indonesia, 2021)
The primary condition of a blessed family is to live in moral holiness and mutual respect for one another. When concern for family members is neglected, what happens is a tragedy that divides the family. Likewise with Noah's family, unable to maintain the integrity of the family due to the dishonor of Ham's behavior. Blessings and curses follow this attitude. This study explores the meaning of Genesis 9:18-29 using the Narrative Method, which is then relevant to the present. This study proves that respect for each family member will bring blessings to the next generation, and vice versa, that disrespect brings division to the family and its descendants.